PENERAPAN KESELAMATAN DAN KESEHATAN KERJA MAHASISWA DI WORKSHOP KAYU JURUSAN TEKNIK SIPIL FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - Bayu Priadi; Fahmi Rizal; Oktaviani Oktaviani; Fitra Rifwan (Universitas Negeri Padang, 2018)
Abstract—. The aim of the research is to find out how the students applied K3 during practicing at workshop of timber Civil Engineering Department FT-UNP. The number of sampling was 33 students, each sampling was accidental sampling. The research is descriptive analyzed by percentages correction. The results showed the applied K3 is well. The results of indicator of the applied K3 on student self is well category as much as (88.2%), the indicator of the tool is well as much as (88.1%), and the indicator of OSH of environment is enough as much as (60.6%). Therefore, it can be conclude that the applied K3 by students is well as much as 76,9%. That means the implementation of K3 is not maximum, it need to improvement to minimize the work accidents.Keywords: Implementation, Occupational Safety and Health, Wood Work Practice